Synthesis of polymeric ionic liquids with unidirectional chain topology by AB step growth polymerization. (24th February 2017) - Suckow, M.; Roy, M.; Sahre, K.; Häußler, L.; Singha, N.K.; Voit, B.; Böhme, F.
Abstract: Poly(ionic liquid)s with alkyl imidazolium moieties in the main chain were synthesized by step growth addition polymerization of the AB monomers 1-(4-chlorobutyl)-1 H -imidazole, 1-(6-chlorohexyl)-1 H -imidazole, and 1-(6-bromohexyl)-1 H -imidazole in the melt. The molar masses of the polymers were controlled by adding 1-butyl-1 H -imidazole as monofunctional chain stopper. The bromine containing monomer polymerized spontaneously at room temperature whereas the chlorine containing monomers were sufficiently stable up to 40 °C. This could be evidenced by DSC measurements which showed a broad exothermal peak above 40 °C caused by the polymerization. MALDI-TOF investigations proved that dissociation of the alkyl imidazolium groups which might disturb the expected directional chain topology (AB-AB-AB…) did not occur. This is an important precondition for the intended cross-linking free grafting reactions of the AB monomers on halide containing polymers without any danger of gelation. Additionally, the results of the MALDI-TOF investigations indicated partial complexation of the polymer with the matrix and structural rearrangements during the measurements which converted the ionic imidazolium moieties into neutral moieties. The thermal behavior of the poly(ionic liquid)s has proved to be dependent on the length of the alkyl linking group between the imidazolium moieties and the type of counter ion. Graphical abstract: Highlights: Poly(ionic liquid)s were obtained by AB step growth addition polymerization. MALDI-TOF MS proved that the AB-AB-AB … chain topology was not disturbed. The MALDI spectrum indicated complexation of the polymer with the matrix. Conversion of the ionic imidazolium moieties into neutral moieties was observed. DSC measurements evidenced inhibited crystallization.